Being a couple and developing the capacity for creative parenting: a psychoanalytic perspective. Issue 2 (3rd May 2020) - Morgan, Mary
ABSTRACT: In this paper, the idea of an internal creative couple is explored in relation to parenting. The internal creative couple is seen as an outcome of psychic development, which may or may not have occurred, been impaired or temporarily lost. Examples of the way this can affect the couple and their parenting are given, elaborated through clinical illustrations. The process of psychic development enabling this capacity is described, highlighting several stages that seem crucial, though it is important to note that this development does not necessarily occur in a linear way, and involves returning to, and reworking at different developmental points in life. Creative couple relating, both internally and as manifested in couple and parenting relationships, is challenging and not always possible. Several reasons why this might be so are given.